Comparison of Outcomes After Percutaneous Coronary Intervention in Elderly Patients, Including 10 628 Nonagenarians: Insights From a Japanese Nationwide Registry (J‐PCI Registry). Issue 5 (5th March 2019) - Numasawa, Yohei; Inohara, Taku; Ishii, Hideki; Yamaji, Kyohei; Kohsaka, Shun; Sawano, Mitsuaki; Kodaira, Masaki; Uemura, Shiro; Kadota, Kazushige; Amano, Tetsuya; Nakamura, Masato
Abstract : Background: Scarce data exist about the outcomes after percutaneous coronary intervention (PCI) in old patients. This study sought to provide an overview of PCI in elderly patients, especially nonagenarians, in a Japanese large prospective nationwide registry. Methods and Results: We analyzed 562 640 patients undergoing PCI (≥60 years of age) from 1018 Japanese hospitals between 2014 and 2016 in the J‐PCI (Japanese percutaneous coronary intervention) registry. Among them, 10 628 patients (1.9%), including 6780 (1.2%) with acute coronary syndrome (ACS) and 3848 (0.7%) with stable coronary artery disease, were ≥90 years of age. We investigated differences in characteristics and in‐hospital outcomes among sexagenarians, septuagenarians, octogenarians, and nonagenarians. Older patients were more frequently women and had a greater frequency of heart failure and chronic kidney disease than younger patients. In addition, older patients had a higher rate of in‐hospital mortality, cardiac tamponade, cardiogenic shock after PCI, and bleeding complications requiring blood transfusion. Nonagenarians had the highest risk of in‐hospital mortality (odds ratio, 3.60; 95% CI, 3.10–4.18 in ACS; odds ratio, 6.24; 95% CI, 3.82–10.20 in non‐ACS) and bleeding complications (odds ratio, 1.79; 95% CI, 1.35–2.36 in ACS; odds ratio, 2.70; 95% CI, 1.68–4.35 in non‐ACS) when referenced to sexagenarians. More important, transradial intervention was an inverse independent predictor of both in‐hospital mortality and bleeding complications. Conclusions: Older patients, especially nonagenarians, carried a greater risk of in‐hospital death and bleeding compared with younger patients after PCI. Transradial intervention might contribute to risk reduction for periprocedural complications in elderly patients undergoing PCI.